Small implants nella protesica di spalla - Stoppani, C.; Randelli, P.S. (Lo Scalpello - Journal, 2019)
SMALL IMPLANTS IN SHOULDER ARTHROPLASTYIn over a century of history, shoulder prosthetics has seen numerous developments in terms of both design and surgicalindications: from the first monobloc hemiarthroplasty proposed by Neer, many innovations have occurred, which ledto the development of complete modular prostheses. Nowadays, anatomic shoulder arthroplasties are able to adapt topatient-specific anatomical characteristics. Reverse shoulder arthroplasty, which revolutionised articularbiomechanics, has provided a possible solution for the treatment of patients with rotator cuff failure. The attempt toreduce complications related to traditional implants and the desire to guarantee greater bone stock preservation havepushed the research towards a progressive reduction in humeral stem length until its complete elimination. At thesame time, researchers have studied and developed surface implants that reduce pain with minimal changes in theoriginal anatomy. Humeral head resurfacing consists in a metal cap that covers the articular portion of the proximalhumeral epiphysis without any substantial osteotomy of the humeral head. Despite their recent introduction, theresults offered by the so-called small implants appear to be very promising and it is reasonable to expect theirsignificant diffusion in the future.